Estimation of the total lipids concentration and fatty acids diagnosis in the tapeworm parasite Postgangesia hemispherous parasitic in European Fishes Silurus glanis from Tigris River-Mousl city - Al-Niaeemi, B. H. S.; Mikael, M. H. (Al-Qadisiyah Journal of Pure Science, 2018)
Concentration of total lipids in each of the tapeworm Postgangesia hemispherous and intestine of its final host, normal and infected European fish Silurus glanis, were estimated. The analysis and diagnosis of fatty acids in the tapeworm have also been studied using Gas- chromatography (GC). The total concentration of lipid in tapeworm tissues was (148.41±0.8) mg/ 100 ml of worm extract, while in intestine of normal and infected final host were (168.003±1.21) and (107.04±1.2) mg/ 100 ml of gut extract respectively. A significant difference between the host, normal and infected fishes was observed at probability level of (p ≤ 0.05). According to retention time of standard esterified fatty acids, the analysis of fatty acids of the tapeworm have showed six fatty acids involved two saturated fatty acids (Plamitic and Stearic acids), three unsaturated fatty acids (Oleic, Linoleic and Linolenic acids), and one unknown fatty acid which was detected but not identified because of the Gas- chromatography has no more than five standard fatty acids. The major fatty acid was the saturated Palmitic one with 69.2 % among the other fatty acids.